The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00402-012-1462-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary clavicle tumors and tumorous lesions: a review of 206 cases in East Asia

Abstract: Clavicle tumors and tumorous lesions in East Asia had an inclined occurrence in respect to age and gender. The most common tumors were eosinophilic granuloma and tumors derived from the bone marrow hematopoietic system. Age of onset was found to be a risk factor for malignancy. These characteristics may be related to the special tissue structures and mode of development in the clavicle as well as to the genetic traits of the typical Mongoloids in East Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 24 publications
5
35
0
Order By: Relevance
“…Other authors have reported high malignancy rates of 51 to 66 % [10, 11], suggesting that physicians should consider the presence of malignancy when a bone tumor is suspected in the clavicle. In a recent large-scale report by Ren et al [6], the benign/malignant ratio was 1.34 among 206 clavicle-origin bone tumors. In the current case, characteristic roentgen imaging findings were suggestive of a GCT; however, the possibility of malignancy could not be completely excluded because of the imaging findings, including PET, and the rare site of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have reported high malignancy rates of 51 to 66 % [10, 11], suggesting that physicians should consider the presence of malignancy when a bone tumor is suspected in the clavicle. In a recent large-scale report by Ren et al [6], the benign/malignant ratio was 1.34 among 206 clavicle-origin bone tumors. In the current case, characteristic roentgen imaging findings were suggestive of a GCT; however, the possibility of malignancy could not be completely excluded because of the imaging findings, including PET, and the rare site of origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the national bone tumor registry in Japan reported two cases of GCTs in the clavicula (1.1 %) from 2006 to 2012 [5]. Although bone tumors rarely occur in the clavicle, a high proportion of those that develop at this site are malignant [6, 7]. Therefore, establishing a list of preoperative differential diagnoses of bone tumors involving the clavicles is often difficult.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the published data revealed that there are two detailed case reports and two case series of clavicular chondrosarcoma, but only the case reported by Nakazora et al1 refers to a primary myxoid extraskeletal chondrosarcoma arising from the clavicle 1,2,6,7. Deik et al8 also reported a case of extraskeletal myxoid chondrosarcoma arising supraclavicularly, causing an interesting clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Tl-201 (thallium), Tc-99m-sestamibi, Tc-99m-tetrofosmin and metabolic positron (PET) radiopharmaceuticals are characterized as tumor seeking agents, and many times have been found to be useful in the initial diagnosis, grading, and post-therapy evaluation of primary bone tumors. Nevertheless, the importance of bone scintigraphy for the evaluation of bone tumors has decreased over the last several years, with the exception of osteosarcomas, where this method is still valuable; however, the accuracy of a bone scan can be increased by using SPECT and SPECT/CT 7,8…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The clavicle is a strange place to tumors has been reported an incidence of 0.45-1.01% of all bone tumors and the experience is limited. 4 The distal femur, proximal humerus, and proximaltibia are the most common sites of occurrence.…”
Section: S257mentioning
confidence: 99%